Influence of temperature on solvents production from whey - Voget, Claudio Enrique (1985)
The influence of temperature on solvent production from whey was investigated by using strains of Clostridium acetobutylicum and butylicum. Higher yields of solvents were observed at 37°C or at 30°C depending on the strain used.